Smart Surveillance System - Gupta, Yash; Mishra, Samriddhi; Sharma, Deepti (International Journal of Computer Sciences and Engineering, 2025)
Motion Detection surveillance system is an advancement in the current era of technology. In this paper, we have proposed a technology to detect objects, to track moving objects, to eliminate noises and to save videos of our interest. This technique will be highly useful for both home and office needs as these areas demand a reliable surveillance system nowadays. The experiments conducted in accordance with proposed methods which are suitable for real-time surveillance system [1]. The main objective of this provide a secure surveillance system in areas such as ATMs or offices where recording takes place only when objects is present (in motion).